Understanding COVID-19 in Wuhan From the Perspective of Cold-Dampness: Clinical Evidences and Mechanisms - Zheng, Yujiao; Jin, De; Lin, Jiaran; Zhang, Yuehong; Tian, Jiaxing; Lian, Fengmei; Tong, Xiaolin (Frontiers in Medicine, 2021)
Traditional Chinese medicine (TCM) has played a significant role in the treatment of coronavirus disease 2019 (COVID-19) in Wuhan City. During the epidemic, Academician Tong Xiaolin suggested a close association of COVID-19 with cold-dampness, an etiological factor in TCM, by summarizing the characteristics of the COVID-19 patients in Wuhan. and the theory of Cold-dampness Plague was proposed. Based on the Cold-dampness Plague theory, a series of TCM drugs, such as Huoxiang Zhengqi Dropping Pills, Lianhua Qingwen Granules Hanshiyi Formula, and Tongzhi Granule were developed for the different stages, namely mild, moderate, severe, recovery, of the COVID-19. In addition, clinical evidences were obtained through randomized clinical trials or retrospective cohort studies. The Anti-SARS-CoV-2 mechanism of the TCM prescriptions were then summarized from the four aspects: targeting the ACE2 and 3CLPro, targeting cytokines, targeting acute immune responses to SARS-CoV-2, and targeting pulmonary fibrosis. Despite the clinical efficacy and therapeutic pharmacology speculation, more studies such as large-scale randomized clinical trials, cell and animal experiments are needed to further verify the theory of the Cold-dampness Plague in COVID-19 patients.